Mixed convective flow of Williamson ternary hybrid ferrofluid through a moving vertical flat plate - Wan Muhammad Hilmi, Wan Rosli; Norhafizah, Md Sarif; Huei, Ruey Ong; Alkasasbeh, Hamzeh Taha; Muhammad Khairul Anuar, Mohamed (UTM Press, 2026)
Present paper studies the characteristics of an upgraded fluid called Williamson ternary hybrid ferrofluid. This fluid comprises three types of nanoparticles which are magnetite, gold and aluminium oxide in a Williamson based fluid in hopes to improve the fluidity and heat transfer of based fluid. Thus, the objective of this research is to understand the capabilities of this upgraded fluid and to determine whether it performs better than the less nanoparticles hybrid fluid. The blood is taken as a based fluid to integrate the pseudoplastic behaviour of Williamson fluid. The physical model developed is interpreted into non-linear partial differential equations then transformed into ordinary differential equations using similarity transformations. Using Runge-Kutta-Fehlberg (RKF45) method, the transformed equations then coded in Maple software. Parameter used to study the behaviour of the fluid are the nanoparticles volume fraction, the magnetic parameter, the moving plate parameter and buoyancy parameter. Comparison with different types of ferroparticle volume fractions are also included in this research. In summary, the Williamson ternary hybrid ferrofluid demonstrates a 2.81% enhancement in fluidity relative to the Williamson hybrid ferrofluid, with both showing comparable heat transfer characteristics when evaluated using the same value moving plate parameter. Magnetic parameter as predicted do reduced the thermal and velocity boundary layer. Buoyancy parameter also showed similar result with magnetic parameter.